PERAN PEREMPUAN DALAM UPAYA BELA NEGARA MENGHADAPI PANDEMI COVID-19 - TATARA, BENY ABUKHAER; RETNANINGSIH, WAHYU SEKTI (Raheema, 2023)
The Covid-19 pandemic is one of the threats to defending the life of the Indonesian nation and state. In facing all forms of disturbing threats, the Indonesian nation adheres to a universal people's defense and security system, so efforts to defend the nation to defend the nation from various existing threats are the obligation and responsibility of the entire Indonesian nation including women. This study aims to analyze the role of women in efforts to defend the country against the COVID-19 pandemic. This research uses qualitative methods with a literature study approach. The results of the study show that women's involvement in efforts to defend the state in Indonesia has existed since colonialism and the war against colonialism. The role of women in efforts to defend the country against the Covid-19 pandemic is realized through the five basic values of defending the country, namely: love for the motherland, awareness of nation and state, belief in Pancasila as the state ideology, willingness to sacrifice for the nation and state, and possessing the initial ability to defend the country.